Factors That Influence Stress Due to Working from Home: A Comparison Based on Gender - Shirlene Jane Nicole; Nur Asikin Samsuddin; Beatrice Jane Anak Ipot; Mohamad Kefli Mohd Amir (Penerbit UMS, 2021)
COVID-19 has a dramatic impact on employees and workplaces around the world including Malaysia. More public and private organizations are offering work from home as an alternative method of working for their employees. This study aimed to identify the factors influencing stress due to working from home in comparison based on gender. Because of the pandemic variables that lead work from home to arise, researchers make a big contribution to stress. Even so, stress has some adverse effects on mental and physical health. The focus of this paper is to highlight the differences between gender on such perceptions and their relationship to the mental and physical of respondents. A survey of 50 respondents was conducted for this study. To get the results, we applied correlation approaches, descriptive analysis, and regression analysis. The reliability statistics Cronbach’s alpha was used to assess the reliability of the scale utilized in this study as well as the internal consistency of the survey questionnaire. This study concludes that there are differences between men and women on perceptions of control and support demands with job stress, stress-related to family life, time and energy in general and institutional factors in particular. This job stress has a relationship to both mental and physical.